Digital-based Persuasive Communication Strategy - Hasri, Novrianti; Dewi, Evie Ariadne Shinta; Lusiana, Elnovani (Peneliti.net, 2024)
This research discusses the digital-based persuasive communication strategies used by OLX Autos in building effective communication with their digital platform users. This research uses a qualitative approach with a case study, and purposive sampling technique is used in the selection of informants, which consists of managers, Regional Heads, OLX Autos employees, and experienced customers. The results showed that OLX Autos successfully integrated strong persuasive principles in their communication strategy, including the use of social proof, creating a sense of urgency, and delivering relevant information. Persuasive communication is key in building effective relationships with consumers and increasing their awareness and interest. OLX Autos also utilizes digital platforms such as social media, websites, and mobile applications to reach a wider audience and provide more compelling messages. The change in OLX Autos' business model that combines traditional and digital concepts brings innovation in used car marketing. The research also highlights the importance of the concept of digital anthropology in the analysis of used car marketing. Through digital data analysis, OLX Autos can understand consumer preferences and needs more accurately. In conclusion, OLX Autos has successfully built an effective digital-based persuasive communication strategy and utilized online platforms to increase consumer awareness and interest, and integrated the concept of digital anthropology in their marketing analysis.